1981
DOI: 10.1111/j.2044-8295.1981.tb02180.x
|View full text |Cite
|
Sign up to set email alerts
|

Left and wrong in adverts: Neuropsychological correlates of aesthetic preference

Abstract: Twenty left-handed and 20 right-handed subjects were found to differ significantly in their preferences for the left-right arrangement of words and pictures in advertisements. The right-handers preferred the picture to the left of the text, while left-handers had no overall preference, but showed a wider range of individual variation. The results are interpreted as demonstrating an influence of hemispheric specialization on everyday aesthetic preferences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

1987
1987
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 19 publications
0
23
0
1
Order By: Relevance
“…He discusses the implications for consumer behavior in five areas: attention processes, pictorial communications, choice behavior, involvement, and individual differences. Ellis and Miller (1981) found that right-handed respondents preferred print ads. with verbal copy on the right and pictorial material on the left.…”
Section: Marketing Applications Of Brain Lateralitymentioning
confidence: 99%
“…He discusses the implications for consumer behavior in five areas: attention processes, pictorial communications, choice behavior, involvement, and individual differences. Ellis and Miller (1981) found that right-handed respondents preferred print ads. with verbal copy on the right and pictorial material on the left.…”
Section: Marketing Applications Of Brain Lateralitymentioning
confidence: 99%
“…As noted earlier, ads with verbal material placed on the right side of the ad and pictorial material on the left are preferred over counterparts that have verbal material on the left and pictorial material on the right (Ellis and Miller, 1981). Thus, both price on left/copy on right and price on right/picture on left ad executions involve optimal executional element placement as far as the non-price portion of the stimulus.…”
Section: Matching Activation Hypothesismentioning
confidence: 77%
“…those toward which the reader is paying only minimal attention) are liked more when placed to the right as opposed to the left of attended written material, while the opposite is true for non-attended pictorial print ads (Janiszewski, 1988). Similarly, ads with written copy material placed on the right side of the ad and pictorial material on the left are preferred over advertisements that have verbal material on the left and an illustration on the right (Ellis and Miller, 1981).…”
Section: Introductionmentioning
confidence: 92%
“…In the investigation which concerned magazine ads, Ellis and Miller (1981) proved that right-handers preferred the "words rightpictures left" configuration while left-handers had no overall preferences. Similar outcomes were obtained by Rettie and Brewer (2000) in the examination concerning a layout of verbal and pictorial elements of the package design.…”
Section: The Role Of Image-text Layoutmentioning
confidence: 99%